IDENTIFIKASI KEBERADAAN COLIFORM DAN ESCHERICHIA COLI PADA ES JERUK KEMASAN (STUDI DI WILAYAH SEKOLAH DASAR KECAMATAN TEMBALANG KOTA SEMARANG) - Prajna Paramita; Martini Martini; Sri Yuliawati (Jurnal Kesehatan Masyarakat (Undip), 2016)
Need of drinking water becomes a matter that can not be separated from human life, even for primary school aged children. Microbiological quality of the snack drink based on SNI is Coliform <3/g, and have negative in Escherichia coli. The purpose of this study is to describe the microbiological quality of citrus ice instants that sold in elementary school areas by the presence of coliform and Escherichia coli. The study design of this research was cross-sectional with study types is descriptive. The number of sample is 39 samples with 39 subject study. The collect of data using laboratory results. The results showed that samples did not qualify of Coliform numbers is 84.6%, while the presence of Escherichia coli is 56.4%. So that the microbiological quality has 33 qualify samples and 6 unqualify samples. Traders in the area of primary school should pay attention to personal hygiene that can be a factor of contamination of citrus ice snacks. Increasing awareness of trader’s personal hygiene practices with routine monitoring from the primary school’s rules is needed.